2000
DOI: 10.1128/jvi.74.20.9712-9716.2000
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccination Prevents and/or Delays Carcinoma Development of Papillomavirus-Induced Skin Papillomas on Rabbits

Abstract: Malignant progression is a life-threatening consequence of human papillomavirus-associated lesions. In this study, we tested the efficacy of papillomavirus early-gene-based vaccines for prevention of carcinoma development of papillomavirus-induced skin papillomas on rabbits. Rabbit skin papillomas were initiated by infection with cottontail rabbit papillomavirus (CRPV). The papillomas were allowed to grow for 3 months without any treatment intervention. Rabbits were then immunized by gene gun-mediated intracut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 33 publications
2
32
0
Order By: Relevance
“…As an example of the value of DNA-based therapeutic vaccines for HPV, Han et al (80) showed that intracutaneous immunisation of rabbits already displaying papillomas with four DNA plasmids encoding CRPV E1, E2, E6, and E7 genes, protected 75% of them from developing invasive carcinoma within 15 months. Liu et al (69) used a chimaeric gene containing a HPV-16 E7 cytotoxic T-lymphocyte (CTL) epitope DNA fused with a heat shock protein gene as a tumour vaccine delivered via an adeno-associated virus (AAV) recombinant.…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…As an example of the value of DNA-based therapeutic vaccines for HPV, Han et al (80) showed that intracutaneous immunisation of rabbits already displaying papillomas with four DNA plasmids encoding CRPV E1, E2, E6, and E7 genes, protected 75% of them from developing invasive carcinoma within 15 months. Liu et al (69) used a chimaeric gene containing a HPV-16 E7 cytotoxic T-lymphocyte (CTL) epitope DNA fused with a heat shock protein gene as a tumour vaccine delivered via an adeno-associated virus (AAV) recombinant.…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…DNA vaccines 547 encoding a combination of viral early proteins may prove more effective than vaccines based on single genes. This is 548 suggested by recent work in the domestic rabbit (with CRPV challenge), in which DNA vaccination with a 549 combination of genes encoding E1, E2, E6 and E7 proved appeared more effective than DNA vaccines encoding only a 550 single protein (Han et al, 1999b). In Han's study, gene-gun vaccination did not elicit detectable humoral responses to 551 the encoded antigens, although T-cell lymphoproliferative responses were seen to each of the encoded antigens.…”
mentioning
confidence: 92%
“…In Han's study, gene-gun vaccination did not elicit detectable humoral responses to 551 the encoded antigens, although T-cell lymphoproliferative responses were seen to each of the encoded antigens. The 552 lack of humoral response to the encoded antigens was seen when DNA was delivered by either intracutaneous gene gun 553 (Han, et al, 1999b), or intramuscular injection (Han et al, 1999a). 554…”
mentioning
confidence: 99%
“…20 In the cottontail rabbit papillomavirus (CRPV) model, immunization of rabbits with DNA plasmid-encoding CRPV E2 prevented the development of skin papillomas. 21,22 These studies support the use of E2 as an immunologic target in vaccines for the protection or therapy of HPV infection and CIN. Thus virus-like particles composed of the viral capsid proteins (L1 and L2) for use in prophylaxis of HPV-associated disease have been modified to include E2 and E7 proteins.…”
mentioning
confidence: 65%